Financing for sustainable urbanization in Asia and the Pacific proceedings of the ADB Asian think tank development forum 2017. (Asian Development Bank, 2017)
The ADB Asian Think Tanks Network held its annual knowledge-sharing event on 2021 September 2017 in Colombo, Sri Lanka. This publication captures the proceedings of the forum, which featured presentations on the regional economic outlook and various financing schemes for urban infrastructure projects. The network, comprising 43 prominent think tanks in Asia, aims to promote knowledge sharing and capacity building toward better policy support for governments.